PREPARATION OF LARGE PLATY PARTICLES OF CO-AL LAYERED DOUBLE HYDROXIDES - Kayano M.; Ogawa M. (My University, 2006)
Cobalt (II) and Al (III) layered double hydroxides were precipitated from homogeneous solutions using urea hydrolysis under hydrothermal conditions. The particle sizes were controlled successfully by changing the reaction temperature and period. It was found that larger particles formed by reactions at lower temperatures over longer reaction periods because the slow urea hydrolysis at lower temperatures suppresses the formation of nuclei in the solution. When the reaction was conducted at 60°C for 100 days, particles >40 µm wide were obtained.
Keywords: HYDROTHERMAL SYNTHESIS; LAYERED DOUBLE HYDROXIDES; PARTICLE-SIZE DISTRIBUTION; UREA HYDROLYSIS